OPTIMIZATION OF SURGICAL TREATMENT TACTICS ACUTE GANGRENO-NECROTIC PARAPROCTITIS - Narzullaev Sh.Sh. (Research Focus International Scientific Journal, 2023)
The article presents the results of treatment of 242 patients who underwent surgery in the multidisciplinary clinic of Samarkand State Medical University in 2015-2022, among them 23 (9.5%) patients were infected with the necrotic form of the disease. Acute paroproctitis of aerobic etiology was observed in 219 (90.5%) patients. The average age of the patients was 63.1±4.9. All patients underwent clinical examination, rectal examination, rectomanoscopy, transabdominal and transrectal ultrasound examination, computed tomography, and bacteriological examination of wound secretions. All patients underwent urgent surgical operations. The results of the examination showed that timely radical surgery, antibacterial and detoxification therapy led to the recovery of the patients.